THU0366 MAGNETIC RESONANCE IMAGING IN COMPARISON WITH CONVENTIONAL RADIOGRAPHY FOR DETECTION OF STRUCTURAL CHANGES TYPICAL FOR SPA – DATA FROM THE ASSESSMENT OF SPONDYLOARTHRITIS INTERNATIONAL SOCIETY (ASAS) COHORT. (June 2019) - Protopopov, Mikhail; Poddubnyy, Denis; Proft, Fabian; Wichuk, Stephanie; Machado, Pedro; Lambert, Robert G; Weber, Ulrich; Pedersen, Susanne Juhl; Ǿstergaard, Mikkel; Sieper, Joachim; Rudwaleit, Martin; Baraliakos, Xenofon; et al.
Abstract : Background: In axial spondyloarthritis, magnetic resonance imaging (MRI) is useful for depicting active inflammatory lesions. The utility of MRI to display structural changes is not that well established. Objectives: Comparison of MRI and conventional radiography of the sacroiliac joints (SIJs) for detection of structural lesions typical for axial spondyloarthritis (axSpA) in an international multireader exercise. Methods: Patients from the ASAS Cohort with symptoms suggestive of axSpA and both radiographs and T1-weighted MRIs of SIJs available for central reading were included. SIJs radiographs were scored by 3 central readers according to the modified New York (mNY) criteria grading system. Structural damage on radiographs was defined as fulfillment of the radiographic mNY criterion (patient level) or presence of grade 2 sacroiliitis (single joint level) (majority decision). MRI scans were assessed for structural changes compatible with axSpA (global statement) and separate changes (erosion, sclerosis, periarticular fat metaplasia and ankylosis) by 7 central readers (majority decision). Absolute agreement between MRI and radiography and Kappa coefficient were determined. Results: Overall, 199 patients (398 joints) were included, 149 (74.9%) had a diagnosis of axSpA. 102 (51.3%) had definite radiographic sacroiliitis, 65 (32.7%) had structural changes suggestive of SpA on MRI (global assessment). The absolute agreement between MRI and radiography was 69.3%, kappa - 0.39 (Table 1 ). Structural damage on radiographs often (48.1% of cases) could not be confirmed by MRI. Among structural lesions, erosions on MRI showed the best discriminative capacity regarding the structural damage on radiographs (Table 1 ). Conclusion: Only modest agreement between MRI and conventional radiography in detection of structural changes typical for SpA in the SIJs was revealed; erosions on MRI showed the best agreement with the presence of definite structural damage on radiographs. Disclosure of Interests: Mikhail Protopopov: None declared, Denis Poddubnyy Grant/research support from: AbbVie, Merck Sharp & Dohme, Novartis, Consultant for: AbbVie, Bristol-Myers Squibb, Janssen, Merck Sharp & Dohme, Novartis, Pfizer, UCB Pharma, Speakers bureau: AbbVie, Bristol-Myers Squibb, Janssen, Merck Sharp & Dohme, Novartis, Pfizer, Roche, UCB Pharma, Fabian Proft Grant/research support from: Novartis, Consultant for: yes but less than 10.000, Paid instructor for: yes but less than 10.000, Speakers bureau: yes but less than 10.000, Stephanie Wichuk: None declared, Pedro Machado Consultant for: Abbvie, BMS, Celgene, Janssen, MSD, Novartis, Pfizer, Roche and UCB, Speakers bureau: Abbvie, BMS, Celgene, Janssen, MSD, Novartis, Pfizer, Roche and UCB, Robert G Lambert Consultant for: Bioclinica, Parexel, Abbvie, Ulrich Weber Consultant for: Abbvie, Susanne Juhl Pedersen: None declared, Mikkel Ǿstergaard Grant/research support from: Abbvie, Celgene, Centocor, Merck, Novartis, Consultant for: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Speakers bureau: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Joachim Sieper Consultant for: Abbvie, Böhringer Ingelheim, Janssen, Lilly, Merck, Mylan, Novartis, Pfizer, UCB., Speakers bureau: Abbvie, Böhringer Ingelheim, Janssen, Lilly, Merck, Mylan, Novartis, Pfizer, UCB., Martin Rudwaleit Consultant for: AbbVie, BMS, Celgene, Janssen, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB Pharma, Consultant for: AbbVie, BMS, Celgene, Janssen, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB Pharma, Xenofon Baraliakos Grant/research support from: AbbVie, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Centocor, Chugai, Janssen, MSD, Novartis, Pfizer Inc, Roche and UCB, Grant/research support from: AbbVie, Pfizer, Merck Sharp & Dohme, UCB Pharma, Novartis, Consultant for: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Chugai, Janssen Biologics, Novartis, Pfizer, UCB Pharma, Galapagos, Speakers bureau: AbbVie, Chugai, Janssen, Novartis, Pfizer, UCB Pharma, Walter P Maksymowych Grant/research support from: AbbVie, Pfizer, Janssen, Novartis, Consultant for: AbbVie, Eli Lilly, Boehringer, Galapagos, Janssen, Novartis, Pfizer and UCB Pharma; Chief Medical Officer for Canadian Research and Education Arthritis